2013
DOI: 10.1186/1476-072x-12-19
|View full text |Cite
|
Sign up to set email alerts
|

Gaining a better understanding of respiratory health inequalities among cities: An ecological case study on elderly males in the larger French cities

Abstract: BackgroundIn recent years, there have been a growing number of studies on spatial inequalities in health covering a variety of scales, from small areas to metropolitan areas or regions, and for various health outcomes. However, few investigations have compared health status between cities with a view to gaining a better understanding of the relationships between such inequalities and the social, economic and physical characteristics. This paper focuses on disparities in respiratory health among the 55 largest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 84 publications
(122 reference statements)
1
9
0
2
Order By: Relevance
“…The relatively small number of ED visits found for Canadian COPD patients would suggest that the use of ED services for COPD patients may fall on the lower end worldwide. Hospitalization rates, hospital readmission rates, and the number of physician visits for Canadian COPD patients were found to be consistent with rates found in the US [ 62 64 ]. Additionally, trends of increasing healthcare resource use as COPD worsens are consistent with worldwide data [ 61 , 65 ].…”
Section: Discussionsupporting
confidence: 73%
“…The relatively small number of ED visits found for Canadian COPD patients would suggest that the use of ED services for COPD patients may fall on the lower end worldwide. Hospitalization rates, hospital readmission rates, and the number of physician visits for Canadian COPD patients were found to be consistent with rates found in the US [ 62 64 ]. Additionally, trends of increasing healthcare resource use as COPD worsens are consistent with worldwide data [ 61 , 65 ].…”
Section: Discussionsupporting
confidence: 73%
“…Similarly, exposure to environmental contaminants derived from biomass fuel burned for cooking, and living in poorly ventilated areas can also increase the risk of COPD among certain Aboriginal groups who follow a traditional lifestyle or live on reserves [ 23 ]. Interactions between smoking, housing conditions and crowding, material and social deprivation [ 24 ], remote location of residence [ 25 ], low education [ 26 ], poor nutrition, and prenatal and childhood exposures to cigarette smoking are likely to be distal and intermediate mechanisms for the higher epidemiological indicators of COPD burden among Aboriginal peoples in our study.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 1, among the 31 articles identified [3570], 10 studies [37, 42, 43, 46, 52, 55, 61, 66, 68, 69] used multivariable linear/non-linear regression models to evaluate the combined effects of multiple chemical and non-chemical stressors, and 7 studies [36, 38, 40, 45, 47, 59, 68] used logistic regression models. In addition, we found 5 studies [49, 56, 57, 63, 67] that used hierarchical/multilevel regression models.…”
Section: Resultsmentioning
confidence: 99%
“…air pollution), Aschan-Leygonie et al . analyzed health data describing hospitalizations of chronic obstructive pulmonary disease and a large set of different indicator variables of both social and environmental stressors using linear correlations and multiple linear regression models in an ecological case study [37]. They found that socioeconomic features may be the major drivers for inequities of respiratory health status in urban units and concluded that better understanding of ‘differences among cities in their entirety’ is essential to develop effective urban policies.…”
Section: Discussionmentioning
confidence: 99%